Feline Niemann-Pick Disease With a Novel Mutation of SMPD1 Gene. Issue 4 (July 2020) - Takaichi, Yuta; Chambers, James K.; Kok, Mun Keong; Uchiyama, Hiroki; Haritani, Makoto; Hasegawa, Daisuke; Nakayama, Hiroyuki; Uchida, Kazuyuki
A 4-month-old female mixed-breed cat showed gait disturbance and eventual dysstasia with intention tremor and died at 14 months of age. Postmortem histological analysis revealed degeneration of neuronal cells, alveolar epithelial cells, hepatocytes, and renal tubular epithelial cells. Infiltration of macrophages was observed in the nervous system and visceral organs. The cytoplasm of neuronal cells was filled with Luxol fast blue (LFB)-negative and periodic acid-Schiff (PAS)-negative granules, and the cytoplasm of macrophages was LFB-positive and PAS-negative. Ultrastructurally, concentric deposits were observed in the brain and visceral organs. Genetic and biochemical analysis revealed a nonsense mutation (c.1017G>A) in the SMPD1 gene, a decrease of SMPD1 mRNA expression, and reduced acid sphingomyelinase immunoreactivity. Therefore, this cat was diagnosed as having Niemann-Pick disease with a mutation in the SMPD1 gene, a syndrome analogous to human Niemann-Pick disease type A.